Feasibility and Oncological Outcome of Preoperative Chemoradiation With IMRT Dose Intensification for Locally Advanced Esophageal and Gastroesophageal Cancer - Innocente, Roberto; Navarria, Federico; Petri, Roberto; Palazzari, Elisa; Vecchiato, Massimo; Polesel, Jerry; Ziccarelli, Antonio; Martino, Antonio; Ubiali, Paolo; Tonin, Dino; Lauretta, Andrea; Belluco, Claudio; et al. (Frontiers in Oncology, 2021)
Purpose: To explore the feasibility and efficacy of a dose intensification with IMRT and SIB in locally advanced esophageal and gastroesophageal cancer (GEJ) Methods and Materials: We retrospectively analyzed a series of 69 patients with esophageal or GEJ cancer treated at our Institute, between 2016 and 2019, with preoperative IMRT and SIB up to 52.5-54Gy in 25 fractions, in 5 weeks and concurrent carboplatin (AUC2) and paclitaxel (50mg/m2), as in the CROSS regimen. Results: All patients completed the planned IMRT-SIB program with a median of 4 (range 1-5) cycles of concurrent paclitaxel/carboplatin. Compliance to IMRT-SIB was 93%, whereas 54% of patients received 4-5 cycles and 87% at least 3 cycles of concurrent carboplatin/paclitaxel. Grade 3 toxicity was reported in 19% of patients. Complete clinical response (cCR) was achieved in 48% and 13% had disease progression after chemoradiation (CRT). Overall, 49% of patients underwent surgery; reasons for non-operation included cCR in cervical tumor location (10%) or cCR and patient decision (13%). A pathologic complete response (pCR) was achieved in 44% of resected patients. Postoperative complications and mortality rates were 21% and 6%, respectively. At a median follow-up of 12 months (6-25), 2-year overall and progression-free (PFS) survival rates were 81% and 54%, respectively. No difference in PFS by histologic type in operated patients was reported. Non-operated cCR patients had higher PFS, including cervical locations and selected cCR patients who decided for non-operation (75% vs 30%, p<0.01) Conclusion: The study reported favourable results in safety and feasibility of the IMRT-SIB dose intensification in our preoperative CRT program. The toxicity was acceptable, allowing a high compliance to intensified radiation doses with dose reduction of concurrent paclitaxel/carboplatin in some patients. The high rate of cCR and pCR suggested this intensified program is effective in the preoperative CRT and, for selected responsive patients, in the non-operative approach to esophageal and GEJ cancer. The 2-year survival rates were promising. A prospective study is being planned to confirm these observations.